AUGMENTED REALITY (AR) FOR VOCATIONAL TRAINING: A HYBRID MODEL FOR DEVELOPING COMPLEX MECHANICAL SKILLS - Vlad Dumitrescu; Larisa Petrescu; Lucian Negru (Journal Neosantara Hybrid Learning, 2025)
The rapid evolution of Industry 4.0 has transformed vocational education, demanding more effective and technology-driven training methods to develop complex mechanical skills. Conventional training often faces limitations in providing realistic practice environments and immediate feedback, leading to skill gaps among vocational students. This study investigates the application of Augmented Reality (AR) within a hybrid training model designed to enhance learners’ mechanical problem-solving and procedural accuracy. The research aims to determine the effectiveness of AR-based hybrid instruction in improving both cognitive understanding and psychomotor skill acquisition among vocational students in mechanical engineering programs. A quasi-experimental research design with pre-test and post-test control groups was employed. Participants included 100 vocational students divided evenly into experimental (AR-assisted hybrid training) and control (traditional hybrid training) groups. The AR component used interactive 3D overlays and real-time guidance through mobile and wearable devices during machine assembly tasks. Data were collected through performance assessments, observation checklists, and self-efficacy questionnaires. Statistical analysis using paired-sample t-tests and ANCOVA revealed significant improvements in procedural precision, task completion time, and learner confidence for the AR group (p < 0.01). Qualitative feedback confirmed that AR supported experiential learning, reduced cognitive load, and improved error recognition during practice. The findings indicate that integrating AR into hybrid vocational training fosters deeper skill acquisition by bridging theoretical knowledge and hands-on application. This model demonstrates a viable framework for scaling immersive learning technologies in technical and vocational education.